Provider payment bares teeth: dentist reimbursement and the use of check-up examinations - Listl, Stefan; Chalkley, Martin (Social science & medicine, 2014)
Oral diseases are one of the most common diseases globally, yet maximizing health benefits from available resources continues to be a pivotal challenge. Similar to recall appointments in many other medical settings, dental check-up examinations are an essential element of regular treatment. Check-ups are important for ensuring good health but their frequent consumption also implies substantial aggregate health care costs. Although it is crucial to determine appropriate utilization amounts, little is known about the role of financial incentives for both patient and provider. Our analyses relied on ten-year administrative panel data from the Scottish National Health Service including about 1.3 million dental treatment claims which were issued between January 1998 and September 2007. Controlling for unobserved heterogeneity, we estimated a series of fixed-effects models to identify the impact of changes in provider payment and patients' cost sharing on check-up utilization. A significantly higher utilization of examinations was observed if dentists were paid fee-for service compared with salary. Comparably little variation in check-up use was attributable to different extents of patient co-payment. These findings establish that different provider payment methods have a substantial impact on check-up utilization. Because recall appointments in many other medical settings have similar features as dental check-ups, these findings may be relevant for health care decision makers who seek to optimize incentive schemes for all kinds of health care.
Gesehen am 18.08.2020